Influence of Chromium Dose and Feeding Regimen on Growth Performance and Carcass Composition of Pigs Housed in a Commercial Environment - J. T. Gebhardt; J. C. Woodworth; M. D. Tokach; J. M. DeRouchey; R. D. Goodband; J. Loughmiller; S. S. Dritz (Kansas Agricultural Experiment Station Research Reports, 2016)
A study was conducted to determine the effects of increasing chromium propionate (KemTRACE Cr; Kemin Industries Inc., Des Moines, IA) and feeding regimen on growth performance and carcass characteristics of finishing pigs housed in a commercial environment. There were a total of 1,206 pigs (PIC 337 × 1050; initial BW = 63.2 lb) with 27 pigs/pen and 9 pens/treatment. Pigs were split by gender upon arrival at the facility, with 4 blocks of each gender and a final mixed gender block. Gender blocks were randomly allotted to groups of 5 pen locations within the barn. Diets were corn-soybean meal-dried distillers grains with solubles-based and were fed in a 5-phase feeding program. Treatments were arranged as a 2 × 2 + 1 factorial with a control diet containing no added Cr, or diets containing either 100 or 200 ppb of Cr fed during the grower (dietary Phases 1 and 2; 63 to 138 lb BW) and/or finisher (dietary Phases 3, 4, and 5; 138 to 307 lb BW) periods. For growth performance, there was no effect of changing Cr supplementation between the growing and finishing periods. Therefore, only linear and quadratic effects of increasing Cr within growth period were considered using all treatments, as well as linear and quadratic effects of the 3 treatments fed increasing Cr for the full duration of the study. Increasing Cr during the grower period decreased (quadratic, P<0.001) ADG and worsened F/G. During the finisher period, increasing Cr tended (quadratic, P = 0.061) to improve F/G, with the best F/G observed in pigs fed 100 ppb. Overall, increasing Cr had no impact on ADG or ADFI; however, F/G was optimized (quadratic, P = 0.018) when pigs were fed 100 ppb of added Cr. Carcass characteristics were not influenced by added Cr level or Cr feeding regimen. In summary, increasing dietary Cr supplementation elicited minor changes in growth performance with the best F/G observed with 100 ppb of added Cr.
Keywords: chromium propionate; duration; finishing pig; level